Relations between student motivation, immersion and learning outcomes in location-based augmented reality settings - Georgiou, Yiannis; Kyza, Eleni A. (My University, 2018)
Technology-rich educational environments are argued to facilitate immersion, which can subsequently contribute to students’ increased learning; however, empirical evidence is often contradictory. The subjective nature of immersion, which can be influenced by students’ individual differences, can provide a plausible explanation which may account for such contradictory findings. Despite the widespread positive claims, research on the relation between immersion and learning is still in its infancy. This study investigates whether the impact of immersion on learning in location-based Augmented Reality (AR) settings is influenced by student motivation. More specifically, this study is focused on the effects of domain-specific motivation and cognitive motivation on experienced immersion in relation to students’ subsequent learning gains in environmental science. Data were collected from a cohort of 135 10th graders, who used an AR app for environmental science learning; data were analyzed using multiple statistical analyses (pretest-posttest comparisons, correlations, regression analyses, cluster analysis). The results demonstrated that immersion was positively predicted by domain-specific motivation and cognitive motivation. In turn, conceptual learning gains were positively related to the level of immersion that students achieved. Implications are discussed along with future research pathways.
Keywords: Cognitive motivation; Domain-specific motivation; Environmental science learning; Immersion; Location-based augmented reality technologies